STRATEGI PELAKSANAAN PEMBELAJARAN BAHASA ARAB DI KELAS ILMU PENGETAHUAN KEAGAMAAN (IPK) PONDOK PESANTREN AL-ITTIFAQIAH INDRALAYA - Ferry Haryadi (Program Studi Pendidikan Bahasa Arab Fakultas Tarbiyah IAI Al-Qur'an Al-Ittifaqiah Indralaya, 2021)
Arabic subjects are very important subjects in the religious science class (GPA) of Al-Ittifaqiah Islamic Boarding School, so in the process of learning Arabic the teacher is required to be able to apply effective methods in order to create active, creative and fun learning. In this study, we will examine the problem of the objectives of learning Arabic in the religious science class (GPA) of the Al Ittifaqiah Islamic boarding school. The research method is using qualitative methods with data collection techniques through observation, interviews and documentation. The results showed that there are some students who are able to understand the material presented, but there are also some students who have not been able to understand because of the different levels of understanding of the students. Then the material presented is good enough because teaching and introducing mufrodat to students is an effective way for students to understand what they are going to learn. A method is chosen and applied by looking at the purpose of the method, which is in accordance with the learning objectives so that the learning objectives can be achieved maximally. Meanwhile, the evaluation consists of daily tests/exams, mid-semester examinations, and end-of-semester examinations. If the test results do not meet the graduation standards, then the teacher makes remedial measures to improve the students' scores. Keywords: Arabic Learning, strategy, Islamic religious science (IPK)